On the Unemployment Output Relation in South Africa: A Non-Linear ARDL Approach - Mazorodze, Brian Tavonga; Siddiq, Noureen (Journal of Economics and Behavioral Studies, 2018)
The central aim of this paper is to establish the asymmetric effects of cyclical output on South Africa’s unemployment rate. To achieve this objective, the non-linear autoregressive distributed lag model (NARDL) is applied on quarterly data spanning the periods 1994Q1-2017Q4. For every 10% economic contraction and expansion respectively according to the results, the response of the labour market is asymmetric in the long-run in that it loses more workers during contraction (10.3%) than it employs during recoveries (8%) supporting the labour market hysteresis. This is particularly true post the 2009 Global crisis suggesting that firms might have become more risk-averse to short-lived recoveries in recent years. The weak response of the labour market during expansions supports IMFâ€™s recent proposition that economic recovery alone may not be enough to address South Africa’s unemployment problem.